The digital origins of dictatorship and democracy information technology and political Islam - Howard, Philip N. (New York ; Oxford University Press : Oxford, 2010)
Around the developing world, political leaders face a dilemma the very information & communication technologies that boost economic fortunes also undermine power structures. This book looks at the role that communications technologies play in advancing democratic transitions in Muslim countries.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 9, 2010).
Keywords: Islamic countries -- Politics and government; Information technology -- Political aspects -- Islamic countries; Internet -- Political aspects -- Islamic countries